2017
DOI: 10.1089/jir.2016.0106
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 and Interferon Gamma Gene Polymorphisms and Hepatitis C Virus–Related Liver Cirrhosis Risk

Abstract: The aim of the study was to evaluate the association between the gene polymorphisms in interleukin-10 (IL-10) and interferon gamma (IFN-γ) genes with susceptibility and severity of hepatitis C virus (HCV) infection among Egyptian patients. Interleukin-10 -592 A/C, -1082 G/A and IFN-γ +874 T/A genotypes were determined in 100 chronic HCV patients and 50 healthy controls using restriction fragment length polymorphism (RFLP) and the amplification refractory mutation system-polymerase chain reaction (ARMS-PCR) res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The TNFA -308G>A and IL10 -1082A>G polymorphisms were not associated with different levels of necroinflammatory activity or with fibrosis score. Several studies have also found no relationship between these polymorphisms in the TNF and IL10 genes and different stages of the disease [ 15 , 16 , 24 , 28 , 33 ]; probably because the disease progression is due to other factors and not only to the host genetic profile.…”
Section: Discussionmentioning
confidence: 99%
“…The TNFA -308G>A and IL10 -1082A>G polymorphisms were not associated with different levels of necroinflammatory activity or with fibrosis score. Several studies have also found no relationship between these polymorphisms in the TNF and IL10 genes and different stages of the disease [ 15 , 16 , 24 , 28 , 33 ]; probably because the disease progression is due to other factors and not only to the host genetic profile.…”
Section: Discussionmentioning
confidence: 99%
“…The TNFA − 308G > A and IL10 -1082A > G polymorphisms were not associated with different levels of necroin ammatory activity or with brosis score. Several studies have also found no relationship between these polymorphisms in the TNF and IL10 genes and different stages of the disease [21,25,28,31,32). Thus, these polymorphisms seem not to in uence the progression of the histopathological processes of chronic HCV infection because in this disease, in addition to the host immunological factors, others factors inherent to the virus act directly on the in ammatory process, causing tissue damage.…”
Section: Discussionmentioning
confidence: 98%
“…The TNFA − 308G > A and IL10 -1082A > G polymorphisms were not associated with different levels of necroin ammatory activity or with brosis score. Several studies have also found no relationship between these polymorphisms in the TNF and IL10 genes and different stages of the disease [21,25,29,30]. Thus, these polymorphisms seem not to in uence the progression of the histopathological processes of chronic HCV infection because in this disease, in addition to the host immunological factors, others factors inherent to the virus act directly on the in ammatory process, causing tissue damage.…”
Section: Discussionmentioning
confidence: 99%